An Assessment of the Impact of the CARIFORUM EU-EPA on CARIFORUM Exports to the EU (2000 to 2017). Issue 6 (2nd November 2021) - Hosein, Roger; Gookool, Rebecca; Saridakis, George
ABSTRACT: The economic literature is limited on the potential impact of the CARIFORUM-EU Economic Partnership Agreement (EPA) on exports of the region to the EU. This article applies a gravity model to assess the effect of the EPA on CARIFORUM exports to the EU for the period of 2000 to 2017. Our results show that under the EPA, the region has not been able to benefit significantly in terms of sustained merchandise exports to the EU. This observation is also made in the context of the declining complementarity between CARIFORUM economies and the EU in the post-EPA period.